2013
DOI: 10.1016/j.ijscr.2013.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Papillary cystadenoma of epididymis: Is there a need for further investigation in unilateral cases?

Abstract: In unilateral cases of papillary cystadenoma of epididymis such as our patient's, literature advocates that no further examinations and expensive genetic testing is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…1 In the majority of cases, PCE develops within the efferent ductules of the head of the epididymis as a partially or completely cystic or solid lesion measuring about 1-3 cm in diameter and is usually asymptomatic. [2][3][4][5][6] However, in symptomatic patients the most common presentation is a painless, slowly growing, scrotal swelling. In rare occasions, they may present with pain or tenderness in the scrotum or are found to have an epididymal nodule during an examination for infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the majority of cases, PCE develops within the efferent ductules of the head of the epididymis as a partially or completely cystic or solid lesion measuring about 1-3 cm in diameter and is usually asymptomatic. [2][3][4][5][6] However, in symptomatic patients the most common presentation is a painless, slowly growing, scrotal swelling. In rare occasions, they may present with pain or tenderness in the scrotum or are found to have an epididymal nodule during an examination for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…4 Only 60 histologically documented cases have been reported in the English-language literature since the original report by Sherrick in 1956. 5 Because of papillary cystadenoma of the epididymis is a rare epithelial tumour and was reported that transformation to cystadenocarcinoma and it can be seen with the von Hippel-Lindau disease, we wanted to present this case.…”
mentioning
confidence: 99%
“…One-third of the patients with VHLD develop a PCE, while 24-45% of VHLD patients develop clear cell RCC. [2,15] Histologically, PCE resembles RCC, with cystic spaces and intracystic papillary projections lined by clear cells. [15] Immunohistochemically, PCE stains positively with soybean agglutinin, which is not observed in RCC.…”
Section: Ajsmentioning
confidence: 99%
“…[2,3] Bilateral PCE is pathognomonic of VHLD. In unilateral PCE, a review of 59 cases by Odrzywolski and Mukhopadhyay found that the association to VHL disease is about 29.3%, compared to the two-thirds of patients found to be positive for VHL disease with bilateral PCE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation